A review of international and national clinical guidelines for the management of patients with endometrial polyps - Mekan R. Orazov; Liudmila M. Mikhaleva; Olga F. Poymanova; Irina A. Mullina (IP Berlin A.V., 2022)
Endometrial polyp (EP) is a common disease of the uterine mucosa in reproductive age, peri- and post-menopause. Hysteroscopy is the primary method of diagnosing EP, and polypectomy is the method of choice for treatment. Despite many years of research on EP, there are still gaps in the understanding of its pathogenesis; approaches to the diagnosis and therapy of EP are not standardized, which makes it difficult for gynecologists to make informed decisions about the management of patients with this disease. It determined the focus of our work. We reviewed clinical guidelines for EP diagnosis and treatment from the American Society of Gynecological Endoscopy, the Norwegian Society for Gynecology and Obstetrics, the draft clinical guidelines "Endometrial polyps" from the Russian Society for Obstetrics and Gynecology (as of July 28, 2022, not approved by the Russian Ministry of Health); as well as the Royal College of Obstetricians and Gynecologists guideline on the management of women with endometrial hyperplasia. The review has led to the conclusion that the recommendations in the current clinical guidelines for the management of women with EP are inconsistent and the diagnostic algorithm for suspected EP is not well-established; the indications for the wait-and-see, surgical treatment of EP are not defined; criteria of high oncological risk requiring surgical treatment of EP are not formulated. Clarifying these issues will help gynecologists make informed decisions about treatment options.